CAPULANAS NA SALA DE AULA: OS SENTIDOS DA FORMAÇÃO DE EDUCADORES(AS) EM MOÇAMBIQUE - Dias, Vera Lúcia Catoto (2006)
This work is a record of the history life of many people. The stories presented here show different identities: fragments lived and memories cherished as oral cultural expressions, written with emotion, images captured on the meetings. These facts and events, organized and jotted down in this work, become alive and acquire a meaning. As far as the meetings were been held, other opportunities were initiated, which were multiplied. The implementation of the Solidarity Literacy Program in Mozambique, PASMO, made possible that this experience were investigated in order to identify the meaning of teachers formation in Mozambique, Africa, and in Brazil. The objective of this work was centered on the development of a new proposal for teachers formation in Mozambique having as central theme the meetings between professional educators that started to wander in new contexts, involving different countries, cultures, languages, and other forms of communication. It was emphasized the knowledge construction based on the local culture, Mozambican languages, and oral tradition. The insertion of the Mozambican women in the teachers formation has been an important form of appropriation of culture, and a factor for social and cultural mobility. It was in the classroom space, on the teaching chores, and on the meetings between the educators that it was constructed, and reconstructed, the specific knowledge that signaled toward new pedagogic practices. The meetings promoted by the educational practice have leaded the way to new paths for educators formation, initially in Brazil and then in Mozambique.(AU)